2001
DOI: 10.1161/01.cir.103.8.1057
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-Derived Plasma Protein, Adiponectin, Suppresses Lipid Accumulation and Class A Scavenger Receptor Expression in Human Monocyte-Derived Macrophages

Abstract: Background-Excessive lipid accumulation in macrophages plays an important role in the development of atherosclerosis.Recently, we discovered an adipocyte-specific plasma protein, adiponectin, that is decreased in patients with coronary artery disease. We previously demonstrated that adiponectin acts as a modulator for proinflammatory stimuli and inhibits monocyte adhesion to endothelial cells. The present study investigated the effects of adiponectin on lipid accumulation in human monocyte-derived macrophages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
700
2
31

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,170 publications
(754 citation statements)
references
References 37 publications
21
700
2
31
Order By: Relevance
“…In mice, the deletion of the adiponectin gene is associated with insulin resistance and neointimal hyperplasia [38]. Further, in vitro adiponectin inhibits monocyte adhesion to endothelial cells likely by reducing the TNF-α mediated inflammatory response [68] and decreasing macrophage to foam cell transformation [69]. Thus, it is possible that decreased adiponectin concentrations play a critical role in the pathogenesis of atherosclerosis via various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the deletion of the adiponectin gene is associated with insulin resistance and neointimal hyperplasia [38]. Further, in vitro adiponectin inhibits monocyte adhesion to endothelial cells likely by reducing the TNF-α mediated inflammatory response [68] and decreasing macrophage to foam cell transformation [69]. Thus, it is possible that decreased adiponectin concentrations play a critical role in the pathogenesis of atherosclerosis via various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Given the worldwide epidemic of the onset of obesity at an early age, it is likely that the contribution of adiponectin in diabesity will tend to increase. In this context, taking into account ACDC variants and adiponectin levels, in assessing further risk of type 2 diabetes and premature CHD [5] may more effectively encourage subjects who could benefit from help in the future to prevent the diseases and to determine a more efficient treatment increasing adiponectin secretion or action. Furthermore, the search for diabesity genes in morbidly obese subjects is crucial to establish the genetic profile of this very high-risk population and for a better understanding of the molecular determinants of metabolic complications of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of insulin resistance, recombinant adiponectin attenuates type 2 diabetes [4]. Adiponectin, in contrast to TNF-α and leptin, is decreased in subjects with increased fat mass [3], type 2 diabetes or CHD [5]. Prospective studies in Caucasians and in the diabetes-susceptible Pima Indian population, showed that subjects with high adiponectin levels were protected against type 2 diabetes (odds ratio [OR] 0.63 in Pima Indians) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologically, serum levels of the protein correlate negatively with cardiac risk factors, positively with HDL-cholesterol and are lower in patients with coronary artery disease than in controls [13][14][15]. Adiponectin accumulates in rat carotid artery walls after balloon injury, but not in healthy vessel walls [16] and has been shown to suppress both the conversion of macrophages to foam cells and the migration of smooth muscle cells [6,17]. Adiponectin-deficient mice develop severe neointimal hyperplasia, that can be attenuated by adiponectin repletion [18] and the protein protects apo-E deficient mice from development of atherosclerosis [19].…”
Section: Introductionmentioning
confidence: 99%